PENGARUH LAMA PRAKTIK DAN PENGETAHUAN DOKTER PRAKTIK MANDIRI TERHADAP PENEMUAN TERDUGA TUBERCULOSIS ANAK DI WILAYAH SURABAYA UTARA - Fildah Alyani; Chatarina Umbul W (Universitas Airlangga, 2018)
Indonesia is the second most populated country with TB in the world. The proportion of Tuberculosis (TB) and adult tuberculosis cases in Indonesia is increasing every year. East Java is ranked second in TB cases in Indonesia. Surabaya is the most common city of TB cases. Therefore, WHO recommends the DOTS program for TB control that focuses on finding and healing TB patients, especially TB children. However, the implementation of this program has an imbalance in the number of adult TB findings and child TB. Factors that influence the discovery of TB suspected children are the length of practice and knowledge of Independent Practice Doctors (DPM). The purpose of this study was to analyze the effect of long time practice and knowledge of Practice Doctor Mandiri on TB child suspected finding. This research is an umbrella research of operational research of child TB treatment network with cross sectional study design. The sampling technique is simple random sampling with the amount of 42 people. Data collection is secondary data using data collection sheets. Data analysis using logistic regression. The result shows that there is a long effect of practice on TB children with p value 0,015 <0,05 and OR value is 8,182. Independent Practice Physician Knowledge has no effect on TB children with p value 0,297> 0,05 and OR 2,125. There is a need for regular socialization of child TB, especially the management of child TB and the commitment of the Independent Practice Doctor to the discovery of TB suspected